2019
DOI: 10.1016/j.repbio.2019.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Imatinib mesylate does not counteract ovarian tissue fibrosis in postnatal rat ovary

Abstract: Chemotherapy may result in ovarian atrophy, a depletion of the primordial follicle pool, diminished ovarian weight, cortical and stromal fibrosis. Imatinib mesylate is an anticancer agent that inhibits competitively several receptor tyrosine kinases (RTKs). RTKs play important roles in cell metabolism, proliferation, and apoptosis. In clinic, imatinib mesylate is also known as an anti-fibrotic medicine. In the present study, the impact of imatinib on the ovarian tissue was investigated by assessing ovarian tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 61 publications
(94 reference statements)
0
1
0
Order By: Relevance
“…Stromal changes such as fibrosis and neovascularization have been suggested as indirect chemotherapy-induced mechanisms of ovarian reserve depletion. Clinical studies have found significant damage to stromal components following exposure to ovotoxic chemotherapy, including obstruction of cortical stromal blood vessels, neovascularization of small, non-mature, disorganized blood vessels in the ovarian cortex surrounding obstructed vessels, and subcapsular focal cortical fibrosis, following exposure to non-sterilizing doses of combined chemotherapy [83][84][85][86]. Increased follicular atresia and collagen deposition [87] and a significant acute reduction of ovarian blood volume and narrowing Important results in human ovaries have been presented by Shai et al They showed follicle activation in vivo in ovaries of patients recently treated (4-12 days) with alkylating agents, as alkylating agent-treated ovaries displayed significant loss of PMFs, and a significant increase in absolute numbers of growing follicles, in addition to activation markers, indicating chemotherapy-induced PMF reserve loss [74].…”
Section: Ovarian Reserve Depletion Caused By Stromal Damagementioning
confidence: 99%
“…Stromal changes such as fibrosis and neovascularization have been suggested as indirect chemotherapy-induced mechanisms of ovarian reserve depletion. Clinical studies have found significant damage to stromal components following exposure to ovotoxic chemotherapy, including obstruction of cortical stromal blood vessels, neovascularization of small, non-mature, disorganized blood vessels in the ovarian cortex surrounding obstructed vessels, and subcapsular focal cortical fibrosis, following exposure to non-sterilizing doses of combined chemotherapy [83][84][85][86]. Increased follicular atresia and collagen deposition [87] and a significant acute reduction of ovarian blood volume and narrowing Important results in human ovaries have been presented by Shai et al They showed follicle activation in vivo in ovaries of patients recently treated (4-12 days) with alkylating agents, as alkylating agent-treated ovaries displayed significant loss of PMFs, and a significant increase in absolute numbers of growing follicles, in addition to activation markers, indicating chemotherapy-induced PMF reserve loss [74].…”
Section: Ovarian Reserve Depletion Caused By Stromal Damagementioning
confidence: 99%